2019
DOI: 10.1002/jnr.24564
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor training with adjuvant testosterone preserves cancellous bone and promotes muscle plasticity in male rats after severe spinal cord injury

Abstract: Loading and testosterone may influence musculoskeletal recovery after spinal cord injury (SCI). Our objectives were to determine (a) the acute effects of bodyweight‐supported treadmill training (TM) on hindlimb cancellous bone microstructure and muscle mass in adult rats after severe contusion SCI and (b) whether longer‐term TM with adjuvant testosterone enanthate (TE) delivers musculoskeletal benefit. In Study 1, TM (40 min/day, 5 days/week, beginning 1 week postsurgery) did not prevent SCI‐induced hindlimb c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 82 publications
(214 reference statements)
2
26
2
Order By: Relevance
“…In this regard, others have reported that IL‐6 protein is released from soleus but not the predominantly fast‐glycolytic extensor digitorum longus (EDL) of mice, using an ex vivo assay, and that IL‐6 protein expression was primarily expressed in small oxidative fibers of the gastrocnemius and not in larger glycolytic fibers (Liang, Drazick, Gao, & Li, ). Furthermore, it should be noted that a profound slow‐oxidative to fast‐glycolytic fiber‐type shift occurs in the soleus in our moderate–severe contusion SCI model within the time frame of our current study (Yarrow, Kok, & Phillips, ) and it remains unclear whether this phenotypic change has any influence on our findings.…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, others have reported that IL‐6 protein is released from soleus but not the predominantly fast‐glycolytic extensor digitorum longus (EDL) of mice, using an ex vivo assay, and that IL‐6 protein expression was primarily expressed in small oxidative fibers of the gastrocnemius and not in larger glycolytic fibers (Liang, Drazick, Gao, & Li, ). Furthermore, it should be noted that a profound slow‐oxidative to fast‐glycolytic fiber‐type shift occurs in the soleus in our moderate–severe contusion SCI model within the time frame of our current study (Yarrow, Kok, & Phillips, ) and it remains unclear whether this phenotypic change has any influence on our findings.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, in rodent models of severe SCI, the use of dynamic histomorphometry has revealed that trabecular bone resorption persists at the distal femur and proximal tibia in the near absence of bone formation throughout the initial one to three-weeks post-SCI [ 44 , 52 , 53 , 54 , 55 , 56 , 57 ], when nearly all the trabecular bone loss occurs. Thereafter, trabecular bone formation renormalizes [ 58 , 59 ] and bone loss slows [ 52 ].…”
Section: Bone Turnover After Scimentioning
confidence: 99%
“…In this study, two-weeks of quadrupedal (q)BWSTT reversed the bone loss that resulted from cast immobilization but did not lessen bone loss that resulted directly from SCI. In a follow-up study, three-weeks of qBWSTT was also shown not to attenuate trabecular bone deterioration after SCI [ 59 ].…”
Section: Effects Of Abpt and Reloading Modalities On Bone After Scimentioning
confidence: 99%
See 1 more Smart Citation
“…First, regenerative medicine may be needed to regenerate the axonal pathways, and second, rehabilitation approaches may be needed to promote functionality of the axons. Several in vivo studies 4,5 using regenerative rehabilitation have already produced better outcomes for nerve regeneration after SCI; however, there are few clinical trials for SCI using regenerative rehabilitation (e.g., cells + motor training [clinicaltrials.gov: NCT03979742, NCT03225625], scaffold + EES [NCT03966794]). Ultimately, there is a need for regenerative medicine approaches to be translated for use in the clinic and to be developed to complement and enhance rehabilitation approaches.…”
Section: Introductionmentioning
confidence: 99%